A Review of the Main Developments in the Neoclassic Theory in Economics over the Last Decades and Its Perspectives (2021)
This article presents a summary of the most important discussions and developments in the neoclassic school in Economics over the last decades. In this sense, the article illustrates the debates regarding methodology, microeconomics and macroeconomics, which have prompted the development of the discipline. Finally, the article shows the prevalence that the neoclassic theory has gained in Economics, which is linked to a pragmatic method, a highly formalized language and an ability to incorporate contributions from other schools of economic thought